Kaleckian conflict inflation with endogenous labor supply. (28th September 2020) - Datta, Soumya; Saratchand, C.
Abstract: We propose a simple but well‐defined Kaleckian model of conflict inflation, consisting of a Kaleckian investment function and conflict inflation, resulting from workers and capitalists making conflicting claims over their shares in output. The bargaining power of workers depends on the rate of employment. The central bank engages in inflation targeting through changes in the interest rate. We establish the existence of an economically meaningful steady state and examine its stability properties both analytically and numerically. We show the possibilities of cyclical trajectories under certain conditions.